Strain-based seismic performance evaluation of prefabricated structures - Seçkin, Aytuğ; Atalay, Hilal Meydanli; Erdoğan, Hakan; Doran, Bilge; Akbaş, Bülent (Springer International Publishing, 2018)
Precast concrete frame systems are widely preferred for the single storey industrial buildings in Turkey and Europe due to its rapid and economical construction practice. Field investigations after past major earthquakes revealed that the damage in such structures was primarily due to the improper detailing in beam-column connections and lack of required lateral stiffness. In this study, two different precast industrial buildings, damaged during the 1999 Marmara earthquake, were numerically investigated. The seismic performances of the buildings were evaluated by using Incremental Equivalent Seismic Load Method and strain-based damage definitions as recommended in Turkish Earthquake Code. The analytical results obtained from performance evaluations are compared with the findings from the field investigations. © 2020 Elsevier B.V., All rights reserved.
Keywords: Incremental equivalent seismic load method; Precast concrete structures; Seismic damage; Strain-based seismic performance